Factors affecting milk yield, milk composition and physico-chemical parameters of ghee in Murrah buffaloes of Punjab region - N, Veena; Wadhwa, Manju; Hundal, J S; Puniya, A K (Indian Journal of Dairy Science, 2020)
The objective of this study was to find out the effects of season, stage of lactation, production status and parity on milk yield, milk composition and physico-chemical parameters of ghee in sixty Murrah buffaloes. Milk samples were collected from individual animal during morning in both summer (August 2016) and winter (February 2017) season. The results indicated that milk yield was significantly influenced by the stage of lactation, production status, and parity. The average fat percentage was significantly affected by season, stage of lactation, production status and parity. However, the protein percentage was affected by the production status and stage of lactation. The Reichert-meissl (RM) value of buffalo ghee was significantly influenced by the season, production status and lactation stage, however, Polenske value (PV) by the season, production status and parity. An effect of season, lactation stage, production status and parity on butyro-refractometer (BR) reading was significant.